(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
In the recent years WIMAX (Worldwide Interoperability for Microwave Access ) technology is widely used for wireless communication system in many countries because it reach set of features with promising broadband wireless access networks. WiMAX is a wireless digital communications system, also known as IEEE 802.16 that is intended for wireless "Metropolitan Area Networks”. WiMAX can provide broadband wireless access up to 30 miles for fixed stations, and 3-10 miles for mobile stations. It is the latest technology which is approved by IEEE 802.16 group, which is a standard for point-to-point and multipoint wireless networking. The MIMO-OFDM is a key technology for next-generation cellular communications as well as wireless Personal Area Network, wireless Local Area Network and broadcasting (DAB, DVB).In this paper an overview of (MIMO) multiple input-multiple-output system and technology is presented. Multiple antenna transmission technology or MIMO system can increase the overall system performance. Multiple Input Multiple Output (MIMO) wireless systems that use multiple transmit and receive antennas allow a gain in reliability and capacity. this paper analysis of the multiple antenna technologies like MISO, MIMO system under different combination of modulation technologies like BPSK, QPSK, with mobile wireless channel AWGN used and the results shows under the bit error rate versus signal to noise ratio.